Taxa endemic to Campania (southern Italy): nomenclatural and taxonomic notes - Del Guacchio, Emanuele; Innangi, Michele; Giacò, Antonio; Peruzzi, Lorenzo; Caputo, Paolo (Phytotaxa, 2020)
The authors briefly discuss about the list of the taxa endemic to Campania (southern Italy) and the typification of their names. The names Santolina neapolitana and Seseli polyphyllum (and other linked names) are lectotypified on herbarium specimens kept at LY and BOLO. A new combination at subspecific rank is proposed for Globularia neapolitana, validating both a previous invalid proposal and an unpublished lectotypification.